Sekrety Zenona Fajfera - Hoffmann , Krzysztof (Przestrzenie Teorii, 2020)
Liberature, the literary project created by Zenon Fajfer and Katarzyna Bazarnik, is usually read from the material perspective, which emphasizes the formal qualities of a work. The article tries to choose a different path. Firstly, it constructs the figure of a secret as the unrevealed foundation of Fajfer’s books. Secondly, it proposes to read this secret in the Marano mode. Hence, the secret of Marano, a Jew who has to conceal his own identity, supported by Jacques Derrida’s observations, becomes a departure point for a new hermeneutic model.